Development of Measures to Improve the Quality of Bank Assets and Passive Management - Rajapov Elyor Eldor o‘g‘li (European Science Publishing, 2024)
This article provides information on the development of measures to improve the quality of management of assets and liabilities of the bank.
Keywords: Finance, Bank, Active, Passive, Money, Credit, Diversification, Sequence.